The Pitch for Baseball: Washington's Plans for Nationals' Stadium - Wharton, Jonathan L. (Washington, DC's Challenges, 2005)
This is the fourth in a series of books dealing with Washington, DC. Like the first three, this also is the outgrowth of special seminars conducted in the Department of Political Science at Howard University. We examine Washington, DC's challenges, because it is vital to know the conditions under which the residents of the most powerful city in the world continue to live, based on sound empirical evidence.
Keywords: dept.psc

Occupational segregation on the playing field: The case of major league baseball - Sack, AL; Singh, P; Thiel, R (Journal of Sport Management, 2005)
Occupational segregation by race and gender, though less common now than in the past, continues to be the norm rather than the exception in the sport industry. The purpose of this study was twofold. First, occupational segregation on the baseball playing field, often referred to as stacking, was discussed in light of human capital and social closure theories. Second, an attempt was made to replicate and extend a multivariate analysis of stacking by Margolis and Piliavin (1999) that challenges the dominant social science paradigm for explaining stacking. The present study uses more recent data than the Margolis and Piliavin study, as well as multinomial logistic regression analysis. The results reveal that stacking persists in Major League Baseball. They also reveal that the effect of race/ethnicity on assignments to playing positions is reduced when one controls for skills and physical characteristics such as speed and power hitting. The implications of this finding for sport management are examined.
Keywords: dept.psc

George F. Kennan and the birth of containment - The Greek test case - Iatrides, JO (World Policy Journal, 2005)
Keywords: dept.psc